Antidepressant‐induced serotonin syndrome in older patients: a cross‐sectional study. Issue 4 (13th May 2022) - Erken, Neziha; Kaya, Derya; Dost, Fatma Sena; Ates Bulut, Esra; Isik, Ahmet Turan
Abstract: Background: Widespread prescription of antidepressants and their resulting role in serotonin syndrome (SS) are of great importance for clinical practice in the elderly. This study aims to investigate possible associations of antidepressant drug‐induced SS with related variables in these patients. Methods: A total of 238 older adults using antidepressants were included. Patients who fulfilled the Hunter Serotonin Toxicity Criteria (HSTC) for SS were considered as the clinical groups (mild, moderate, or severe), and those who did not as the control group. We recorded all patients' demographic and clinical characteristics, including age, gender, comorbidity index, number of medications, daily equivalent dose of the relevant antidepressant according to fluoxetine per day, electrocardiogram test results, laboratory results, and management. Results: The mean age of all patients was 75.4 ± 7.6 years and 63.4% were female. Sixty patients had SS, while 178 patients did not. There was a significant difference between those with and without SS in terms of gender, frequency of combination antidepressant therapy, and daily equivalent antidepressant dose ( P  < 0.05). The most common diagnostic findings in SS patients were tremor and hyperreflexia and 31.7% was mild, and moderate in 68.3% with higher median age and number of medications ( P  < 0.041). Antidepressants were discontinued in all patients regardless of severity, of whom 71.7% were treated with benzodiazepines and 36.7% with cyproheptadine. After adjusting for age and sex, association with use of SSRI + SNRI, use of any combination therapy, and daily equivalent dose remained significant. Conclusions: The widespread single or combined use of antidepressants in older adults represents an increased clinical concern for SS and physicians should be aware of this drug‐related complication in older patients.